Treatment of Condylomata Acuminata Using a New Non-Vapor-Generating Focused Ultrasound Method following Imiquimod 5% Cream - Jacek Calik; Tomasz Zawada; Torsten Bove (Karger Publishers, 2022)
Condylomata acuminata is the most common sexually transmitted disease in the world. Physical treatments include excision, cryotherapy, electrocautery and ablative CO2, and Nd:YAG laser ablation, while topical treatments include imiquimod immunotherapy and antimitotic podophyllotoxin or sinecatechins. Efficacies of all methods are low, and recurrences are very common. A new combined method is presented as a single case in a 25-year-old male patient diagnosed with numerous condylomas on the penis, scrotum, and lower abdomen. The treatment consisted of a 7-week topical monotherapy using 5% imiquimod cream followed by local treatment with 20 MHz high-intensity focused ultrasound on remaining recalcitrant lesions. Results showed resolution of approximately 70% of the condylomas after imiquimod treatment, and full resolution of all recalcitrant condylomas treated subsequently with high-intensity focused ultrasound. The method is concluded to be safe and effective and, furthermore, presents a new physical method that does not generate airborne infectious human papillomavirus particles that pose a health risk for the medical team performing therapy. Further studies in larger populations are recommended to confirm the combined efficacy of the proposed method.